Study of occurrence of noncompliance with prescription writing requirements and medication errors in outpatient department pharmacy in HUSM Kubang Kerian / Mohamad Shafiq Mat Salleh, Mohd Izat Amir Khoshar Khan and Nik Nurqistina Nik Nordin - Mat Salleh, Mohamad Shafiq; Khoshar Khan, Mohd Izat Amir; Nik Nordin, Nik Nurqistina (2011)
Medication errors are one of the critical problems happen in medical field and still remain as a big challenge to the medical practitioners. In this study, new prescriptions received by an outpatient pharmacy department of a teaching hospital in Kelantan were analysed retrospectively for noncompliance with prescriptions writing requirements as well as to identify the types of medication error. The study involved screening of prescriptions for 5 days period, from 26th September 2010 to 30th September 2010 involving 1290 manual prescriptions from various clinic and unit. Of the 1290 prescriptions, 763 errors were found. Generally, the errors of omission (incomplete information) are the most frequent happened which is made up of 717 errors (94%) out of total errors involving incomplete prescriber details (name, signature, official stamp), patient details (name, age, registration number), date, incomplete document, illegible handwriting, route of administration, dose, frequency, strength, unit of strength, dosage form, duration of therapy and diagnosis. The errors of commission (wrong information) detected was only 46 (6%), involving wrong drug name, unauthorized abbreviations, route of administration, dose, frequency, strength, unit of strength, dosage form, and drugs interaction. Although the errors of omission are not hazardous, but still the need for improvement is important because the total of 717 errors happened for 5 days is quite a big number. In conclusion, it is very clear that the role of pharmacist is great in preventing and minimizing the medications errors beside the needs of correct prescription writing and other strategies by all of the health care components.